Igbo Traditional Food System: Documentation, Uses and Research Needs - Okeke, E.C.; Eneobong, H.N.; Uzuegbunam, A.O.; Ozioko, A.O.; Kuhnlein, H. (Pakistan Journal of Nutrition, 2008)
The Igbos live in southeastern Nigeria and number over 23 million with population densities ranging from 300 to over 1000 persons per kilometer, the highest in West Africa. As a first step towards solving the problems of stunting and micronutrient deficiency, this study sought to document traditional foods in terms of availability in seasons and their use in Igbo culture area. Eight communities selected from four States were used for the study. Key informant interviews, focus group discussions and questionnaires were used to document and ascertain use of local foods by households. About 294 species and over 400 varieties of foods were documented. The results show that, for the Igbos, maize and rice are the major cereals consumed. The foreign rice syndrome has in the recent past overtaken many households, especially in the urban areas. Twenty one (21) species of starchy roots and tubers, 20 legumes, 21 nuts/seeds, 116 vegetables, 12 mushrooms and 36 fruits were documented of which 9, 3, 7, 12, 0 and 11 respectively were found in food composition tables. Cereals, starchy roots and tubers are important food groups for the Igbo people. They are available all year round but are more abundant during the harvest season. They form the base of the diet of Igbo culture area. Most commonly consumed legume is the cowpea (Vigna unguiculata). Local varieties of cowpea and other species of legumes are also available but not produced in large quantities. The scientific names of most of the mushrooms have not been found. Fruits were not main parts of the diet but were eaten outside regular meals. Two types of oil (red palm oil and vegetable oil) were documented. A total of 21 condiments and spices were identified. Some of these condiments are soup thickeners and are high in dietary fiber. Animal foods were about 27 species for meat/poultry/eggs, 12 species of fish and 3 species of insect/larvae were documented. Milk and milk products were not mentioned. Availability and seasonality determined the consumption of these foods by the Igbo people. In all Igbo communities, foods are eaten not only for their nutritional values but also for their medicinal and socio-cultural significance.